ANALISIS PENGARUH PENERAPAN PRINSIP ERGONOMI PADA MOTOR CHOPPER DARI STANG HINGGA JOK: ANALYSIS OF THE EFFECT OF ERGONOMICS PRINCIPLE APPLICATION ON CHOPPER MOTORCYCLES FROM HANDLEBARS TO SEAT - wara, gusti; F.X.Wara Wangge, Gusti; Rande, Thadeus; Yosep Boli Odung, Bernadus (Blueprint Journal, 2026)
This study evaluated the suitability of chopper motorcycle designs to the anthropometrics of 40 male users aged 20–25 at Cristo Re Polytechnic. Measurements of five body parameters showed high variation in size, and all variables were found to be non-normally distributed based on the Shapiro–Wilk test (p < 0.05). Ergonomic analysis revealed that several motorcycle dimensions did not match the body characteristics of the majority of users. The 110 cm handlebar height was 15 cm below the actual hand reach height (125 cm), causing shoulder elevation and increasing static load. The 70 cm handlebar-seat distance also exceeded the ideal reach (62 cm), forcing the rider to lean forward, increasing shoulder and back muscle tension. Furthermore, the footrest, positioned far forward, overextended the legs and increased pressure on the hips and lower back. These findings indicate an increased risk of fatigue and musculoskeletal disorders. Design recommendations include raising the handlebars to 130–135 cm, reducing the handlebar-seat distance to approximately 62 cm, and lowering the footrest by 5–10 cm with an increase of approximately 3 cm in height to achieve a more ergonomic riding posture.